Pencegahan Kekerasan terhadap Anak di Sekolah melalui Pola Asuh Islami - Hani Sholihah; Sri Nurhayati (Society, 2022)
This study aims to find a method of Islamic parenting styles, as an effort to prevent violence against children in schools. With the literature study method, verses from the Quran and Hadith are studied to obtain a formulation of Islamic parenting in Islamic families. The formulation is then applied as an effort to protect children in the school environment. The research found that parenting in Islamic families is carried out as early as possible before a child is born. The parenting style not only includes physical and intellectual aspects, but also includes emotional and spiritual aspects. The verses of the Quran and Hadith hint at the values of education in the Islamic family which include aspects of “aqidah”, worship, and morals. The Quran also mentions that parenting should be done by giving role model and teaching wisdom to children. These educational values can shape children into a piety person, has the nature of “ihsan” and “istiqomah” and far from any violence attitudes. Children are also educated to not only be individual children, but also to have concern for others. With comprehensive aspects of education through Islamic parenting in Islamic families, children are educated to become individuals of character and noble character. Thus, acts of violence against children in schools can be prevented.